Analysis of Beef Marketing in Lafia Metropolis of Nasarawa State, Nigeria - Kassali, R.; Philip, DOA; Yesufu, A. O.; Abdul, S. O. (Journal of Marketing Studies, 2018)
Purpose: The study analysed the marketing of beef in Lafia metropolis. Specifically, the study described the socio-economic characteristics of beef marketers in the area, analysed the market structure for beef, assessed the marketing cost and profit, and estimated the operational efficiency of beef marketing and its determinants. It also identified the constraints faced by beef marketers in the area. Methodology: Data used for the study were generated through administration of well structured questionnaire to 60 respondents made up of 20 wholesalers and 40 retailers randomly selected from 4 major beef markets in the study area. Data were analysed using descriptive statistics, budgeting, concentration ratios, Gini coefficient, operational efficiency and regression technique. Results: Results showed variation in marketing cost, marketing margin and marketing profit for both wholesale and retail beef markets. Results also indicated that wholesale beef market operated at a monopoly level while the retail beef market showed perfect competition. The Gini coefficient for wholesalers of 0.47, which is above 0.35 indicates high level of market concentration and high inequality in wholesale beef market, while retail market with a value of 0.29 shows low level of market concentration and low level of inequality. Wholesalers were also more operationally efficient than retailers. The result further showed that transportation cost had significant effects on marketing efficiency for the wholesale market. But transportation cost, record keep, level of education and packaging cost has significant effect on operational efficiency of beef retail market. Results also indicated that marketers both wholesalers and retailers complained of inadequate capital as a very serious constraint; transportation cost and inadequate storage facilities, as serious constraints; risk of spoilage, low patronage as not serious constraints, and market charges as not very serious constraints.